Analysis of entrepreneurial intention among students in business schools of Bangladesh - Naim, Sayada Jannatun (International Journal of Management and Business Studies, 2022)
This article was published in The International Journal of Management and Business Studies and the definite version is available at: http://www.ijmbs.com/Vol8/issue1/3-sayada-jannatun-naim.pdf The Article's website is at: http://www.ijmbs.com/